Efektivitas Ekstrak Daun Salam (Syzygium polyanthum) Dalam Mencegah Kenaikan Kadar Kolesterol LDL Tikus Putih (Rattus norvegicus) Diinduksi Kuning Telur Puyuh - Baiq Isti Hijriani; Bustanul Atfal; Liah Kodariah; Nurul Hadiatun; Nurul Khatimah Ismatullah (Jurnal Kesehatan Rajawali, 2023)
Quail egg yolk contains high cholesterol which can trigger dyslipidemia. If Cholesterol is consumed in excess, will increase lipid profile, which can increase LDL cholesterol levels. Bay leaf extract contains several active compounds, like quercetin, a class of flavonoids with antioxidants that can prevent LDL oxidation. The aim of this study is to ensure the effectiveness of bay leaf extract on LDL cholesterol levels in white rats induced by quail egg yolk. The animal tested in this study were male white rats (Rattus norvegicus) with the Sprague Dawley strain. Samples were randomly selected and divided into five groups: three groups given quail egg yolk and bay leaf extract in various doses of 0.18 g/day, 0.36 g/day and 0.72 g/day, positive control given quail egg yolk, and negative control without treatment. The ANOVA test showed that there were significant results between the treatment groups, positive control and negative control (p<0.05). Next, the BNJ test showed that giving bay leaf extract (0.18 g/day, 0.36 g/day) had a significant effect on LDL cholesterol levels (p<0.05), while a dose of 0.72 g/day showed that not significant (p>0.05), so we can conclude that the dose of 0.72 g/day was the most effective in preventing an increase in LDL cholesterol levels.